Medium chain fatty acid supplementation improves animal metabolic and immune status during the transition period: A study on dairy cattle - Wang, Zhonghan; Wang, Qianqian; Tang, Chuanlan; Yuan, Jing; Luo, Chenglong; Li, Dong; Xie, Tian; Sun, Xiaoge; Zhang, Yan; Yang, Zhantao; Guo, Cheng; Cao, Zhijun; et al. (Frontiers in Immunology, 2023)
This study aimed to determine the effects of dietary supplementation of medium-chain fatty acids (MCFAs) on immune function, metabolic status, and performance of transition dairy cows. Twenty multiparous Holstein cows were randomly assigned to two treatments at 35 d before calving. 1) CON (fed the basal diet), 2) MCFA treatment (basal diet was supplemented at an additional 20 g MCFAs mixture every day) until 70 d after calving. The results showed that the serum amyloid A and myeloperoxidase concentrations in the blood of cows in MCFA treatment were significantly decreased during the early lactation (from 1 d to 28 d after calving) (P = 0.03, 0.04, respectively) compared with the CON, while the tumor necrosis factor α concentration was significantly decreased at 56 d after calving (P = 0.02). In addition, the concentration of insulin in the pre-calving (from 21 d before calving to calving) blood of cows in MCFA treatment was significantly decreased (P = 0.04), and the concentration of triglyceride also showed a downward trend at 28 d after calving (P = 0.07). Meanwhile, MCFAs supplementation significantly decreased the concentrations of lithocholic acid, hyodeoxycholic acid, and hyocholic acid in the blood at 1 d after calving (P = 0.02, < 0.01, < 0.01, respectively), and the level of hyocholic acid and taurocholic acid concentrations (P < 0.01, = 0.01, respectively) decreased dramatically at 14 d after calving. However, compared with the CON, the pre-calving dry matter intake and the early lactation milk yield in MCFA treatment were significantly decreased (P = 0.05, 0.02, respectively). In conclusion, MCFAs supplementation in a transition diet could improve the immune function and metabolic status of dairy cows, and the health of transition cows might be beneficial from the endocrine status.